Effect of ethephon stimulation and fertilizer applications on nutrient dynamics of rubber clones in South Sumatra, Indonesia - Risal Ardika; Pearl Sanchez (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Soil is a critical factor in determining fertilizer efficiency. Rubber tree requires a stable environment to achieve optimal growth and production. The research aimed to evaluate how fertilization and ethephon stimulation affected the nutrient dynamics of rubber in various clones. The Indonesian Rubber Research Institute experimental field in South Sumatra served as the site for the research. Three replications of the experiment were set up using a split-plot design with three factors. The rubber clones were the primary plot, with ethephon stimulation and fertilization rate as subplots. The rubber clones used in this research, namely GT 1, BPM 24, PB 260, and IRR 112, were planted in 2011 (8 years) with a 6 x 3 m planting spacing on the existing rubber plantation. Several rates of fertilization were used in the experiment: 50% recommended rate (50 RR), 100% recommended rate (100 RR), 150% recommended rate (150 RR), and control (no fertilizer). During the observation period, ethephon stimulation was administered at a rate of S/2 d3 ET2.5% 6/y (half spiral cut, tapped downward every 3 days with ethephon stimulation of 2.5% active ingredient and application of 1 g per tree on groove, six times per year at monthly intervals) every two months. Observation parameters were soil nutrient analysis (soil pH, cation exchange capacity (CEC), C-Organic, total nitrogen, available phosphorus, and exchangeable bases (K, Ca, Mg), and leaf nutrient analysis (N, P, K). Results showed that soil properties were improved by fertilization after a year of treatment. Organic-C, CEC, total nitrogen, available phosphorus, and exchangeable cation increased across rubber clones. Tissue analysis in leaves and nutrient content also showed significant differences between fertilization and stimulation treatments in all clones. Further research is required on which chemical fertilizers with biological fertilizers can induce low nutrient availability in poor soil conditions. Keywords: rubber clones; ethephon stimulation; fertilizer rate; nutrient dynamics; soil properties